Increased hepatic progenitor cell response and ductular reaction in patients with severe recurrent HCV post‐liver transplantation. Issue 6 (6th May 2016) - Sclair, Seth N.; Fiel, Maria Isabel; Wu, Hai‐Shan; Doucette, John; Aloman, Costica; Schiano, Thomas D.
Abstract: Objectives: Post‐liver transplant (LT) hepatitis C virus (HCV) patients may develop allograft cirrhosis and rarely fibrosing cholestatic hepatitis (FCH), while others have a stable course. Hepatic progenitor cells (HPC) may be implicated in liver injury and fibrogenesis through ductular reaction (DR). We studied HPC response and DR in three distinct post‐LT patterns of HCV: stable recurrence, allograft cirrhosis, and FCH . Methods: We identified 52 patients with untreated recurrent HCV and longitudinal liver biopsies (20 stable /23 cirrhosis /9 FCH ) and eight healthy controls. Archived liver biopsy specimens for three time points (LT; initial recurrence; and clinical outcome) were stained for cytokeratin‐7. Manual HPC counts and DR quantification using image analysis were performed. Results: HCV counts and DR at LT did not differ across groups. At initial recurrence, HPC expansion occurred only in patients who developed cirrhosis, while prominent DR was present in those who developed FCH vs. stable and controls (p < 0.05). At outcome biopsies, HPC response and DR were increased in cirrhosis and FCH vs. stable and controls (p < 0.05). HPC response and DR did not differ in stable vs. controls. Conclusions: These findings suggest that an altered HPC response assessed by cytokeratin‐7 stain after LT may predict severity of HCV recurrence.